Applying Problem Based Learning educational method for improving Human-tech competencies in Computer Engineering students: a research proposal - Ribeiro, Nuno (2012)
This paper resumes the background theory of the likewise entitled research project. The project aims to give a contribution to software programming quality improving “Human-tech” competencies in Computer Engineering students as a means to prevent, or at least avoid in a great extend, the rate of unsuccessful software implementation projects. We are specially interested in researching what Human Factors competencies must be profiled in Computing Curricula outcomes that may contribute to better prepare students as “Human-tech” experts. We will apply Problem Based Learning educational method for delivering those competencies to students. We believe it is possible to do better than what as been done, to have a better degree of adequacy between the Human user and the software he uses for his/her activity. All background theory that support the axiomatic principles of this research project is explained in the first section. Then the project is outlined as well as its plan and expected outcomes and contribution in the following sections.